The Relationship between Culture and E-Learning Adoption among UTHM Students. - Salim, Siti Aisyah; Mohd Isa, Nor Asyikin Fadliana (Research in Management of Technology and Business, 2021)
Understanding students’ needs is important especially for successful implementation of e-learning adoption. There are several factors that influence the adoption of e-learning. However, only few studies have investigated cultural factors in specific. Thus, this study aims explore the relationship between cultural factors and intention to adopt e-learning among UTHM students. Technology Acceptance Model (TAM) is adopted as theoretical background for this study. About 140 undergraduate UTHM students has answered the survey questions. The data has been gathered using quantitative research method where self administrated questionnaire and online survey been applied. Statistical Package for Social Science (SPSS) software been used to get the demographic information, variables and the relationship between cultural dimensions and intention of adoption. From the analysis, it showed that power distance, individualism collectivism, masculinity femininity and uncertainty avoidance have a positive significant relationship towards e-learning adoption. This study can be used by other researchers to understand more on the adoption of e-learning especially on cultural aspects.